Exceptional Courts in Iraq (1958-1968) Historical study (Journal of the College of Basic Education, 2022)
The exceptional courts constituted an important event in the contemporary history of Iraq, and the exceptional courts were defined as the courts that are formed in exceptional circumstances and are competent to adjudicate in certain matters according to a special legal text. Its formation came for political goals and the establishment of a court that is not subject to the restrictions of judicial work, legal applications, and the guarantees it provides to the accused, which guarantee the methods and fair trials. These courts represented a clear violation of the individual freedoms guaranteed by the Iraqi constitutions, as these courts issued sentences against hundreds of Iraqis who oppose the regime or belong to parties. In addition, it exercised illegal or legitimate means of investigation and arrest.